PENGGUNAAN LEMBAR KERJA PESERTA DIDIK (LKPD) LIVE WORKSHEET DALAM MENINGKATKAN HASIL PEMBELAJARAN SOSIOLOGI PESERTA DIDIK KELAS X-IPS SMA NEGERI 2 PEKAT KABUPATEN DOMPU - Surnaningsih, Sri (CV Sintesia, 2024)
The objective of the research is to discover and explain the effectiveness of using LKPD (student’s worksheet) live worksheet to improve learning result in Sociology of grade X-IPS students at SMA Negeri 2 Pekat. The research is classroom action research, conducted in two cycles. Each cycles consisted of four stages. The units of analysis of the research were students of grade X-IPS at SMA Negeri 2 Pekat in Dompu with the total of 20 students. The qualitative and quantitative data were takem from, the observation, students’ test result and documentation. The results suggest that using LKPD live worksheet can improve the result of students’ learning in sociology. This is evidenced by an increase in the result of students’ learning from the final test cycle I obtained an average of 47 or 31% then increased in the final test evaluation cycle II with an average value of 81 or 72%. The results of this classroom action research can be concluded that using LKPD live worksheet has succeeded in improving the result of students’ learning in sociology of grade X-IPS SMA Negeri 2 Pekat in Dompu Academic Year 2021/2022.